2008
DOI: 10.1007/s11325-008-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of sleep apnea based on single night of polysomnography vs. two nights of polysomnography

Abstract: Utilizing a large patient population, this study supports the significant night-to-night variability in PSG respiratory variables. Identification of sleep apnea in some patients is reduced when sleep experts are provided with only one PSG recording. The clinical implication is that about 13% of sleep clinic patients might benefit from a second night of PSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 15 publications
3
81
0
3
Order By: Relevance
“…33 Our review identified nineteen studies that evaluated the performance of the Berlin Questionnaire against PSG in the identification of patients with OSA. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The studies were conducted in a wide variety of geographic locations including Brazil, 38 Canada, 34,42 Greece, 37 Iran, 36 Korea, 40 Turkey, 43 and the United States. 41,44 Various patient populations were considered, including those in primary care clinics, sleep clinics, the veteran population, and patients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…33 Our review identified nineteen studies that evaluated the performance of the Berlin Questionnaire against PSG in the identification of patients with OSA. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The studies were conducted in a wide variety of geographic locations including Brazil, 38 Canada, 34,42 Greece, 37 Iran, 36 Korea, 40 Turkey, 43 and the United States. 41,44 Various patient populations were considered, including those in primary care clinics, sleep clinics, the veteran population, and patients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…34,[129][130][131] There was a wide range of OSA severity within the populations included in the four studies (AHI range: 7-34). None of the studies included data on body position during the 2 nights of PSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is more prevalent than asthma and diabetes mellitus in adults (Ahmadi et al, 2009). OSAHS is associated with several cardiovascular diseases including arterial hypertension, acute myocardial infarction, and stroke, and increases cardiovascular mortality and morbidity (Yaggi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%